2022
DOI: 10.1021/acs.inorgchem.2c02560
|View full text |Cite
|
Sign up to set email alerts
|

Synergizing Cobalt Ruthenium Alloy with Chromium Oxyhydroxide for Highly Efficient Electrocatalytic Water Splitting

Abstract: Constructing a coupling interface of multicomponents with different functions is of considerable importance for designing an advanced bifunctional water splitting electrode. Particularly, designing and developing alloy/oxyhydroxide-integrated electrodes have emerged as a tendency yet remain a considerable challenge. In this work, a novel 3D nanostructure electrocatalyst assembled from CoRu nanoalloy and CrOOH nanosheets (denoted as CoRu-CrOOH/NF) was directly grown on nickel foam via a successive hydrothermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…[43][44][45][46] 0.21 and 0.23 nm lattice spacings could be observed in HR-TEM images (Fig. 1e), which was attributed to hexagonal CoRu (002) and CoRu (100) facets, 28,[47][48][49] and indicated that MOFs and a PDA shell could act as a growth template for CoRu alloy NPs. In addition, EDS elemental mapping further conrmed the uniform distribution of Ru, Co and N atoms in the material (Fig.…”
Section: Synthesis and Characterizationmentioning
confidence: 93%
“…[43][44][45][46] 0.21 and 0.23 nm lattice spacings could be observed in HR-TEM images (Fig. 1e), which was attributed to hexagonal CoRu (002) and CoRu (100) facets, 28,[47][48][49] and indicated that MOFs and a PDA shell could act as a growth template for CoRu alloy NPs. In addition, EDS elemental mapping further conrmed the uniform distribution of Ru, Co and N atoms in the material (Fig.…”
Section: Synthesis and Characterizationmentioning
confidence: 93%
“…Alloying with platinum group metals (PGMs) is a versatile strategy to boost the catalytic activity of nonprecious transition metals. Alloys are available to tailor the reactivity of the active sites to optimize the adsorption/desorption of catalytic intermediates, thereby drastically lowering the activation energy barrier (Figure a). Ruthenium (Ru) is not only the cheapest PGMs but also possesses hydrogen evolution activity close to that of Pt, representing an ideal alloying metal for performance enhancement. Normally, small-sized nanoalloys (<5 nm) not only possess high atomic utilization and distinctive electronic structures but also feature abundantly exposed unsaturated active sites and high specific surface areas, thus presenting remarkable catalytic properties. , At present, alloys are prone to agglomerate to form large-sized particles under the general thermal synthesis conditions, which severely limits their catalytic activity, resulting in rarely alloyed catalysts capable of yielding ampere-level current densities for HER at low overpotentials. Therefore, it remains a challenge to construct highly dispersed, small alloy nanostructures with high performance. Porous organic polymers (POPs) are tunable molecular materials formed through covalent bonding of organic monomers, serving as molecular templates for fabricating various types of metal nanostructures. POPs can anchor metal species with the coordination atoms on the frameworks, limiting their agglomeration and growth in thermal synthesis, thus decreasing the size of metal nanoparticles (NPs). , In addition, the porous carbon layers derived from POPs function as favorable carriers for metal NPs and stabilize their active structures. , Therefore, POPs are expected to furnish promising molecular templates for architecting small alloys with great dispersibility.…”
Section: Introductionmentioning
confidence: 99%
“…The exploitation of new inorganic catalytic materials for efficient overall water splitting via accelerating the two half-reactions, namely, hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), is of great significance for the development of the hydrogen economy. To date, Ir/Ru oxides and metallic Pt are still the benchmark catalysts for OER and HER in terms of activity and stability, respectively. , In an integrated electrolyzer, the practical implementation of monofunctional electrocatalysts is usually limited by the mismatched working conditions . It is also noted that the development of efficient bifunctional catalysts for both OER and HER in the same solution is necessary, based on the fact that device fabrication can be simplified and thus the cost can be reduced. , However, most of the developed bifunctional electrocatalysts currently can be applied in only alkaline electrolytes. To survive under a strongly acidic and oxidative environment for acidic overall water splitting at faster kinetics, the use of noble metals as the electrocatalysts is indispensable. In spite of the wide application of noble metals, , individual Ir/Ru oxides or metallic Pt is monofunctionally active with regard to water splitting ut supra. , Designing bifunctional activities of noble metals remains challenging. In addition, the change in the proton concentration on one electrode is inevitable during water splitting processes, and thus, the bifunctional noble metal catalysts are also required to be efficient over a wide pH range.…”
Section: Introductionmentioning
confidence: 99%